Introduction to Special Collection "The Exceptional Arctic Stratospheric Polar Vortex in 2019/2020: Causes and Consequences". Issue 18 (20th September 2022) - Manney, Gloria L.; Butler, Amy H.; Wargan, Krzysztof; Grooß, Jens‐Uwe
Abstract: This paper introduces the special collection in Geophysical Research Letters and Journal of Geophysical Research : Atmospheres on the exceptional stratospheric polar vortex in 2019/2020. Papers in this collection show that the 2019/2020 stratospheric polar vortex was the strongest, most persistent, and coldest on record in the Arctic. The unprecedented Arctic chemical processing and ozone loss in spring 2020 have been studied using numerous satellite and ground‐based data sets and chemistry‐transport models. Quantitative estimates of chemical loss are broadly consistent among the studies and show profile loss of about the same magnitude as in the Arctic in 2011, but with most loss at lower altitudes; column loss was comparable to or larger than that in 2011. Several papers show evidence of dynamical coupling from the mesosphere down to the surface. Studies of tropospheric influence and impacts link the exceptionally strong vortex to reflection of upward propagating waves and show coupling to tropospheric anomalies, including extreme heat, precipitation, windstorms, and marine cold air outbreaks. Predictability of the exceptional stratospheric polar vortex in 2019/2020 and related predictability of surface conditions are explored. The exceptionally strong stratospheric polar vortex in 2019/2020 highlights the extreme interannual variability in the Arctic winter/spring stratosphere and the far‐reaching consequences of such extremes. Plain Language Summary: The Arctic stratospheric polar vortex—a band of strong winds roughly encircling the pole at about 65°N latitude from about 15 to 50 km above the Earth's surface that forms every winter—was exceptionally strong during the 2019/2020 winter. The strong vortex in the stratosphere was linked to unusual conditions at both higher and lower altitudes. This collection of papers explores the far‐reaching consequences of the exceptionally strong stratospheric polar vortex in 2019/2020, including impacts on Arctic chemical ozone loss and on surface weather conditions. Chemical ozone loss in spring 2020 matched or exceeded the most previously on record (for 2011) and showed some features similar to the larger loss that occurs over the Antarctic every spring. The exceptionally strong stratospheric polar vortex was linked to weather extremes, including record heat, unusual patterns of precipitation, marine cold air outbreaks, and windstorms. Key Points: The stratospheric polar vortex in 2019/2020 was the strongest and longest‐lasting on record as described in this special collection This exceptionally strong and cold polar vortex led to unprecedented Arctic ozone loss, approaching that in some Antarctic winters Circulation anomalies linked to the vortex spanned the mesosphere to the surface with implications for extreme weather and predictability